Altered Lnc-EGFR, SNHG1, and LincRNA-Cox2 Profiles in Patients with Relapsing-Remitting Multiple Sclerosis: Impact on Disease Activity and Progression - Mohamed S. Attia; Heba A. Ewida; Mohamed Aly Abdel Hafez; Shohda A. El-Maraghy; Maha M. El-Sawalhi (Diagnostics, 2023)
Relapsing–remitting multiple sclerosis (RRMS) is the most prevalent MS subtype. Ample evidence has indicated that long noncoding RNAs (lncRNAs) are crucial players in autoimmune and inflammatory disorders. This study investigated the expression of lnc-EGFR, SNHG1, and lincRNA-Cox2 in RRMS patients during active relapses and in remission. Additionally, the expression of FOXP3, a master transcription factor for regulatory T cells, and NLRP3-inflammasome-related genes were determined. Relationships between these parameters and MS activity and annualized relapse rate (ARR) were also evaluated. The study included 100 Egyptian participants: 70 RRMS patients (35 during relapse and 35 in remission) and 30 healthy controls. RRMS patients showed significant downregulation of lnc-EGFR and FOXP3 and dramatic upregulation of SNHG1, lincRNA-Cox2, NLRP3, ASC, and caspase-1 compared to controls. Lower serum TGF-β1 and elevated IL-1β levels were observed in RRMS patients. Notably, patients during relapses displayed more significant alterations than those in remission. Lnc-EGFR was positively correlated with FOXP3 and TGF-β1 and negatively correlated with ARR, SNHG1, lincRNA-Cox2, and NLRP3 inflammasome components. Meanwhile, SNHG1 and lincRNA-Cox2 were positively correlated with ARR, NLRP3, ASC, caspase-1, and IL-1β. Excellent diagnostic performance for lnc-EGFR, FOXP3, and TGF-β1 was demonstrated, while all biomarkers exhibited strong prognostic potential for predicting relapses. Finally, the differential expression of lnc-EGFR, SNHG1, and lincRNA-Cox2 in RRMS patients, especially during relapses, suggests their involvement in RRMS pathogenesis and activity. Correlation between their expression and ARR implies relationships to disease progression. Our findings also highlight their promising roles as biomarkers for RRMS.